Associations Between Habitual School-Day Breakfast Consumption Frequency and Academic Performance in British Adolescents - Adolphus, Katie; Lawton, Clare L.; Dye, Louise (Frontiers in Public Health, 2019)
Studies indicate that breakfast positively affects learning in children. The present study aimed to examine associations between habitual school-day breakfast consumption frequency and academic performance, as measured by the General Certificate of Secondary Education (GCSE). The GCSE is a national academic qualification obtained by most British children during secondary education. Adolescents aged 16-18 years (n=294; females: 77.2%) completed a retrospective 7-day food diary to report breakfast intake and a questionnaire to report GCSE grades. Breakfast was defined as any food or drink containing ≥5% of total energy expenditure (TEE) consumed up to 10:00am on school days. Habitual weekly school-day breakfast consumption frequency was categorized as rare (0-1 school days), occasional (2-3 school days) or frequent (4-5 school days). GCSE grades were aggregated into point scores and linear regression models were applied. Participants’ GCSE grades in Mathematics and English were analyzed using ordinal logistic regression. Adolescents who rarely consumed breakfast on school days had a significantly lower capped point score (β= -0.13, p<0.05) and mean point score (β= -0.14, p<0.05) compared with frequent consumers. Low/middle socio-economic status (SES) adolescents who rarely consumed breakfast were significantly less likely to achieve higher Mathematics grades compared to low/middle SES adolescents who frequently consumed breakfast (adjusted cumulative odds ratio (OR): 0.35 95% confidence interval (CI): 0.17-0.72). This cross-sectional study demonstrates that habitual school-day breakfast consumption amongst adolescents is a significant correlate of GCSE attainment. The results offer promising associative evidence which warrants further exploration in well controlled studies.